THE ROLE OF SCHOLARS IN MEDIATING BETWEEN SALAH AL-DIN AL-AYYUBI AND OTHER ISLAMIC FORCES - Safanah Jasim Mohammedal-Gburi; Aeshah jasim ismael (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The research dealt with the study of the role of scholars in the mediation between Salah al-Din al-Ayyubi and other Islamic forces located specifically in the Levant and the Euphrates Island. Through it, we touched on the most prominent mediations that brought together Salah al-Din with the Zangids and Artuqids, and the most prominent scholars participating in them, such as Kamal al-Din al-Shahrazuri, Baha al-Din Ibn Shaddad and others. Accordingly, the research was divided into two axes. The first dealt with mediation between Salah al-Din al-Ayyubi and the Zangids, and the second was devoted to the mediation between Salah al-Din al-Ayyubi and the Artuqids. We concluded the research by reviewing the most important results the researcher reached.